JAM KERJA KARYAWAN TERHADAP PERILAKU TIDAK AMAN DI PT JUNACON BALIKPAPAN (STUDI KASUS: PT JUNACON) - Lubis, Tyas Rawadi (IDENTIFIKASI, 2020)
PT Junacon is a company engaged in the general contractor sector. Based on the preliminary observations that the researchers have done, it is found that the excess work hours of workers are 12 hours to 14 hours a day, this is due to the completion of achieving work targets. The research method was carried out with a quantitative approach, to find the relationship between employee working hours (variable X) and unsafe behavior (variable Y). The number of samples is 32 workers. The linear regression results showed a strong, positive and unidirectional relationship with the t value> t table, namely 6.442> t table 2.042. The relationship between these two variables can indicate that the excessive number of working hours can cause workers to behave unsafe. It can be concluded that both the X variable and the Y variable are related to the t value of 6.442.